Nurses’ Experiences of End-of-Life Care in ICU - Fransisca Romana Ratnasari; Janet Citra Maria; Yenni Ferawati Sitanggang (Fakultas Keperawatan Universitas Andalas, 2025)
Caring for a dying patient creates some unavoidable circumstances. However, nurses will continue to face this situation as part of their nursing activities or responsibilities. Often, the care to dying patients will involve the feelings of nurses and might cause stressful conditions to. This study aims to explore the nurses’ experiences in end-of-life care to the dying patients in the ICU. This study was qualitative; a semi-structured interview was used to explore the experiences of nurses in the ICU about end-of-life care. Five ICU nurses were interviewed based on their experiences in taking care of patients during the end of life. All interviews were recorded, transcribed, and used to analyze the data based on the content. Categories and subcategories were retrieved from the statements of the data. Three categories retrieved from this study: struggle with self-emotion, providing holistic care to family members, and challenges in providing end-of-life care. Some suggestions obtained from this study are that nurses need to increase their knowledge and skills in end-of-life care. It is also suggested that health institutions develop an end-of-life protocol to enable nurses to prepare themselves for what should be done for their dying patients and their family members.